In vitro functional characterization predicts the impact of bacterial root endophytes on plant growth. (21st May 2022) - Tran, Tri; French, Elizabeth; Iyer-Pascuzzi, Anjali S
Abstract : Traits of bacterial root endophytes can predict an isolate's impact on plant root and shoot growth promotion. Abstract: Utilizing beneficial microbes for crop improvement is one strategy to achieve sustainable agriculture. However, identifying microbial isolates that promote crop growth is challenging, in part because using bacterial taxonomy to predict an isolate's effect on plant growth may not be reliable. The overall aim of this work was to determine whether in vitro functional traits of bacteria were predictive of their in planta impact. We isolated 183 bacterial endophytes from field-grown roots of two tomato species, Solanum lycopersicum and S. pimpinellifolium . Sixty isolates were screened for six in vitro functional traits: auxin production, siderophore production, phosphate solubilization, antagonism to a soilborne pathogen, and the presence of two antimicrobial metabolite synthesis genes. Hierarchical clustering of the isolates based on the in vitro functional traits identified several groups of isolates sharing similar traits. We called these groups 'functional groups'. To understand how in vitro functional traits of bacteria relate to their impact on plants, we inoculated three isolates from each of the functional groups on tomato seedlings. Isolates within the same functional group promoted plant growth at similar levels, regardless of their host origin or taxonomy. Together, our results demonstrate the importance of examining root endophyte functions for improving crop production.